Association of Kawasaki Disease Shock Syndrome with Giant Coronary Artery Dilatation – Presentation of Two Cases and A Literature Review - Bejiqi, Ramush; Bejiqi, Hana; Retkoceri, Ragip; Maloku, Arlinda; Mustafa, Afderdita; Bejiqi, Rinor R. (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction Kawasaki disease is an acute, self-limited vasculitis of childhood characterized by fever, bilateral nonexudative conjunctivitis, erythema of the lips and oral mucosa, changes in the extremities, rash, and cervical lymphadenopathy. Coronary artery aneurysms or ectasia develop in approximately 15 to 25% of untreated children with the disease and may lead to myocardial infarction, sudden death, or ischemic heart disease. Despite an overlap of clinical features with toxic shock syndrome, children with Kawasaki disease generally do not develop chock. Cases Here we report two old children who presented with a toxic shock-like illness, and were diagnosed with Kawasaki disease when coronary artery abnormalities were found on transthoracic echocardiography, recently reported as a “Kawasaki disease shock syndrome”. Relevant articles about KD and shock were collected and demographic data, clinical presentation, laboratory variables, echocardiogram findings, treatment and special features were analyzed when available. Conclusion Pediatrics cardiologist should be aware of this potentially severe form of manifestation of the Kawasaki disease. Key words Kawasaki disease, Kawasaki disease shock syndrome, coronary artery aneurysm, intravenous immunoglobulin,